Humans and Other Animals in the Middle Ages : An Introduction and Reader - Line, Philip, (Explorations in Medieval Culture ;, 2025)
This sourcebook serves both as an introduction and a wide-ranging reference work for human attitudes to nonhuman animals in Latin Europe during the Middle Ages. Under twelve headings, it includes numerous translated passages from Latin and vernacular texts that reflect human conceptions and uses of other animals during the period 300-1520. Theologians, philosophers, encyclopaedists, bestiarists, hagiographers, chroniclers, huntsmen and writers of agricultural manuals, cookbooks and plague treatises all had something to say about the place of nonhuman animals in their world and their interaction with humans, or simply recorded incidentally what they did in their writings. All are represented here.